Energy efficient QoS routing for mobile ad hoc networks. (2018) - Saravanan, R.
Many researchers developed several routing techniques to reduce the power consumption of the nodes without decreasing capacity of the network, to increase life time of the network while preserving the connectivity of nodes. A routing protocol is presented in this paper that reduces overall energy consumption of nodes in the mobile ad hoc networks. This routing protocol focuses on energy conservation and also it provides some of the necessary quality of services in routing such as throughput, packet delivery ratio and less error rate. This routing protocol utilises the bandwidth of the network effectively and finds the minimum energy consuming path that has less error rate. Recharging capability of the nodes is taken into consideration while computing minimal energy consuming path from source to destination. The protocol is simulated for various network parameters using a network simulator. The performance of proposed protocol is evaluated by comparing the simulation results with the results of one of the popular routing protocols such as DSR.